Nanopharmaceutical advanced delivery systems - Dave, Vivek; Gupta, Nikita; Sur, Srija (Wiley-Scrivener, 2021)
"The book provides a single volume covering detailed descriptions about various delivery systems, their principles and how these are put in use for the treatment of multiple diseases. It is divided into four sections where the first section deals with the introduction and importance of novel drug delivery system. The second section deals with the most advanced drug delivery systems like microbubbles, dendrimers, lipid-based nanoparticles, nanofibers, microemulsions etc., describing the major principles and techniques of the preparations of the drug delivery systems. The third section elaborates on the treatments of diverse diseases like cancer, topical diseases, tuberculosis etc. The fourth and final section provides a brief informative description about the regulatory aspects of novel drug delivery system that is followed in various countries"- Resumé vydavatel